Mission hospital responses to challenges and implications for their future role in India's health system - Caleb Flint; Vijay Anand Ismavel; Ann Miriam (Health for All Nations, 2020)
Background: Mission hospitals in low-resource regions of the world face significant challenges in providing high-quality, accessible care to patients. External funding is limited and can fluctuate significantly from year to year. Additionally, attracting and retaining well-qualified healthcare professionals for more than short stints can seem almost impossible. Located in a remote region in Northeast India, the Makunda Christian Leprosy & General Hospital has developed a model over the past 25 years that has enabled it to sustainably expand access to high-quality care for the region's poor, which we evaluate in this paper. Methods: We combine an external assessment by a research team at the Wharton School of Business with internal insights from two leaders at Makunda Hospital to evaluate the Makunda Model. The external assessment included 31 in-depth, on-site interviews of patients, employees, and competitor hospital administrators; physical observation of Makunda's facilities and operational practices; and an analysis of years of financial documents and hospital statistics. Results: We studied the impact of the Makunda Model on volumes, efficiency, quality, and community impact. In 2018-19, Makunda Hospital provided 109,549 outpatient visits, 14,731 hospital admissions, 6,588 surgeries (2550 major), and 5,871 baby deliveries in a 162-bed facility with a bed occupancy rate of 88%. The hospital operates with an annual budget of $2.7M ($1 = INR 75.70) and receives only 2.5% of its operating revenue from external sources. The hospital has developed a strong reputation in the community and beyond for providing excellent maternal care and catering to the poor. Discussion: The hospital's business model revolves around two key business strategies: (a) poor-centric strategies and (b) thoughtful cost management. Innovative poor-centric strategies include "ability-to-pay"-based pricing, equal services for all (in contrast to a freemium model), hyper-tailored charity (using the "shared meals" and "vital assets" tests), and community engagement. Thoughtful cost management is accomplished by "revised gold standard" treatment protocols and recruitment and retention of an efficient workforce. Conclusion: We conclude that Makunda Hospital's unique combination of poor-centric strategies and thoughtful cost management have enabled it to achieve the volumes necessary to sustainably improve access to care for the poor in Northeast India.